Implementasi Cyber Public Relations BNN Provinsi Kalimantan Timur dalam Upaya Mengedukasi Masyarakat Mengenai P4GN - Pusparini, Faradilla; Boer, Kheyene Molekandella (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
In the digital era, the education process is not only through conventional media. BNN East Kalimantan Province can utilize online media as a means of public education because of its greater potential in disseminating information about P4GN. The aim of this research is to find out, analyze and describe the implementation, efforts and obstacles faced by East Kalimantan Province BNN public relations in implementing cyber public relations in public education regarding P4GN. This research uses a qualitative type of research, a case study approach with indicators of the five basic elements of cyber public relations, namely transparency, internet porosity, the internet as an agent, content richness, and reach. The data analysis technique used is the Miles and Huberman data analysis model. The research results show that East Kalimantan Province BNN Transparency has carried out information disclosure according to the needs of the community and agency interests, East Kalimantan Province BNN Internet Porosity has never experienced data leaks. The internet as an agent for the BNN of East Kalimantan Province carries out very little content collaboration with stakeholders, content collaboration occurs with BNNK work staff. The wealth of BNN East Kalimantan Province content has provided various forms and types of information regarding P4GN. Reach BNN East Kalimantan Province using the business account on the online media Instagram @infobnn_prov_kaltim to see the reach of the content.